Biosensitivity and Theoretical Electronic Structure Investigations on 3-(2-Hydroxyphenyl)-2-iminothiazolidin-4-one and Its Zn2+ and Cd2+ Metal Complexes - Zewdu Bezu Gemechu; Boobalan Maria Susai; Abi M. Taddesse; Endale Teju Bedada; R. Ramamoorthy (Journal of Chemistry)
A two-step cyclocondensation reaction has been carried out using 2-aminophenol with 2-chloroacetyl chloride to produce o-hydroxyphenyl chloroacetamide followed by treatment with KSCN in CH3COCH3 to produce the heterocyclic ligand 3-(2-hydroxyphenyl)-2-iminothiazolidin-4-one. The Zn2+ and Cd2+ complexes with a metal : ligands ratio of 1 : 4 were synthesized in ethanol using respective metal precursors with the title ligand. Antimicrobial activities of the ligand and its complexes were checked against some bacterial and fungal strains. The result evidenced better bioactive performance of the metal complex (though lower than the standard drug) than the free ligand against Escherichia coli, Staphylococcus aureus, and Salmonella typhi bacteria, as well as Fusarium oxysporum and Aspergillus niger fungal strains. Theoretical investigations on ligand and metal complexes help to infer the electronic structure behavior of them. Molecular geometry and bond order analysis provides detailed information on the nature of chemical structure and bonding. Molecular Electrostatic Potential (MEP) and atomic charge analysis claims evidence on charge distribution and electrophilic, nucleophilic reactive sites. Natural bond orbital analysis provides second-order perturbed stabilization interactions, orbital population, and their energies. Other theoretical properties such as hardness, softness, electron affinities, and ionization potential were derived and discussed in detail.